Dissolved black carbon in aquatic ecosystems - Wagner, Sasha; Jaffé, Rudolf; Stubbins, Aron (Limnology and oceanography letters, 2018)
The incomplete combustion of organic molecules produces a chemically diverse suite of pyrogenic residues termed black carbon (BC). The significance of BC cycling on land has long been recognized, and the recognition of dissolved BC (DBC) as a major component of the aquatic carbon cycle is developing rapidly. As we seek a greater understanding of DBC cycling, our interpretation of environmental DBC concentrations and molecular composition should take into account both the formation conditions of charred residues, and the physico‐chemical transformation of DBC that occurs during transit within aquatic systems. We present the current state of knowledge concerning sources, processing, and sinks of DBC in inland, coastal/estuarine, and ocean waters. We feature studies and new methodologies which focus specifically on the aquatic cycling of DBC, explore the relationship between particulate and dissolved BC, and highlight research gaps which should be targeted to advance our current knowledge of DBC biogeochemistry.